If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3 = 2x + -5 Reorder the terms: 3 + 8x = 2x + -5 Reorder the terms: 3 + 8x = -5 + 2x Solving 3 + 8x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 8x + -2x = -5 + 2x + -2x Combine like terms: 8x + -2x = 6x 3 + 6x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 6x = -5 + 0 3 + 6x = -5 Add '-3' to each side of the equation. 3 + -3 + 6x = -5 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = -5 + -3 6x = -5 + -3 Combine like terms: -5 + -3 = -8 6x = -8 Divide each side by '6'. x = -1.333333333 Simplifying x = -1.333333333
| 21x^2+13x=8 | | x^2+10=-7 | | 4x-12=3x-6 | | 4x-12=-3x-6 | | -3x+5=1x-5 | | y^4-13y^3=42y^2 | | 6=.5+2 | | 2m-3+m=15 | | 24n(n-1)=0 | | x^2-17x+84=0 | | 3x^2-x-6=0 | | -12x-4(5+10x)=11(-3x+12) | | 9x=5x+9x-15 | | c(c-17)=0 | | 3x+6=2x+9 | | 4=-0.8 | | 5x+5=5x+x+2 | | 10x+6=6x-8+10x-16 | | 12*11-20= | | 16x-9=5x+12x-20 | | 10x+9-11-x=-2(2x+4)-3(2x-2) | | 5*1+2*(3-1)=6 | | n-14n-6=-5 | | n-14n-6=-6 | | 4x+3=5x+4x-3 | | 5=2x+5x-2 | | 5*5-(25/5)=20 | | 5*5-(25/5)= | | 4=4x-2+2x | | 75=3(6x-5) | | 9x-9=3x+6+x+6 | | 5x+45+-89=90+41 |